How New Individuals Behave in a Heterogeneous Community: A Computational Approach to Norm Assimilation Using Agent-Based Systems - Mahmoud M.; Ahmad M.S.; Mostafa S.; Subramainan L. (Springer New York LLC, 2023)
Computation theory; Intelligent robots; Intelligent systems; Machine design; Software agents; Agent-based systems; Computational approach; Future designs; Human social interactions; Human society; Social groups; Social issues; Social norm; Social robots